An Analysis of Poverty Reduction Program Based on the Conditional Cash Transfer (CCT) (A Case of the Family Hope Program Implementation in Pandak Bantul District 2014) - Ahmad Hanif (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2016)
The study of this research was an analysis of the public policy implementation concerning on the implementation of the Family Hope Program (PKH) in Pandak, Bantul regency in 2014. The purposes of this study were to investigate: (1) the implementation of the Family Hope Program (PKH), (2) the performance of the Family Hope Program (PKH) and (3) factors that influence the performance of the Family Hope Program (PKH). To investigate the implementation of the Family Hope Program in Pandak, the researcher tried to analyze the processes during its implementation. While to measure the performance of the Family Hope Program in Pandak, the researcher applied policy output indicators approach from Randall B. Ripley. It consists of indicators of access, scope, accountability, be as, promptness of service and suitability of the program needs. The research used a qualitative method by using primary data and secondary data. To collect the data, the researcher used observation, interview and documentary. To analyze the data, the researcher applied inductive data analysis. PKH implementation consists of some the steps, those are: (1) determining the targets, (2) validating and preparing of the initial meeting, (3) the distributing of aid and clustering the participants of PKH,(4) commitments verification, and (5) updating the data. From the various stages taken, there is a problem related to the weaknesses of the validation process, that it is only administratively. The weak validation process leads the determination of the target program became less accurate. Based on the measurement of the policy output  indicators showed that the output performance of the Family Hope Program (PKH) in Pandak is low, it can be seen from: 1) aspect of bias, as there are still economically, some established families belonging to the members of PKH; 2) aspects of delivery service (promptness of service) as the lateness of the financial aid disbursement, and 3) aspects of the sustainability of the program with the needs of the target group, the aid criteria or the amount of aid considered to be unfair for each RTSM.The research results also showed five dominant factors toward the performance of the program, namely: 1) the lack of communication with the local village government; 2) the lack of data transparency of the PKH receiver targets; 3) the limitation of the available sources; and 4) the absence of mechanisms and rules controlling the fund spent by RTSM; and 5) the decreased compliance of RTSM in fulfilling the obligations under the rules of the program. According to these factors, there were some recommendations to increase the policy / program to be better, those are: (1) Improving the communication and involving the local village government, (2) Increasing the data transparency of the PKH receiver targets; (3) there should be an audit of the available sources; (4) Social Ministry should issue a new rule and control it to the spending of PKH financial aid by RTSM, and (5) optimizing the functions and the coordination between the supervisors and the local village government to increase the awareness of the poor society in fulfilling the specified obligations in the program.